137Cs tracing of the spatial patterns in soil redistribution, organic carbon and total nitrogen in the southeastern Tibetan Plateau - Zhengan Su; Lijuan Wang; Yihan Liu; Bin Fu; Jianhui Zhang; Zuo Wu; Tao Zhou; Junjie Wang (International Soil and Water Conservation Research, 2023)
The southeastern Tibetan Plateau, which profoundly affects East Asia by helping to maintain the stability of climate systems, biological diversity and clean water, is one of the regions most vulnerable to water erosion, wind erosion, tillage erosion, freeze–thaw erosion and overgrazing under global climate changes and intensive human activities. Spatial variations in soil erosion in terraced farmland (TL), sloping farmland (SL) and grassland (GL) were determined by the 137Cs tracing method and compared with spatial variations in soil organic carbon (SOC) and total nitrogen (total N). The 137Cs concentration in the GL was higher in the 0–0.03 m soil layer than in the other soil layers due to weak migration and diffusion under low precipitation and temperature conditions, while the 137Cs concentration in the soil layer of the SL was generally uniform in the 0–0.18 m soil layer due to tillage-induced mixing. Low 137Cs inventories appeared at the summit and toe slope positions in the SL due to soil loss by tillage erosion and water erosion, respectively, while the highest 137Cs inventories appeared at the middle slope positions due to soil accumulation under relatively flat landform conditions. In the GL, the 137Cs data showed that higher soil erosion rates appeared at the summit due to freeze–thaw erosion and steep slope gradients and at the toe slope position due to wind erosion, gully erosion, freeze–thaw erosion and overgrazing. The 137Cs inventory generally increased from upper to lower slope positions within each terrace (except the lowest terrace). The 137Cs data along the terrace toposequence showed abrupt changes in soil erosion rates between the lower part of the upper terrace and the upper part of the immediate terrace over a short distance and net deposition on the lower and toe terraces. Hence, tillage erosion played an important role in the soil loss at the summit slope positions of each terrace, while water erosion dominantly transported soil from the upper terrace to the lower terrace and resulted in net soil deposition on the flat lower terrace. The SOC inventories showed similar spatial patterns to the 137Cs inventories in the SL, TL and GL, and significant correlations were found between the SOC and 137Cs inventories in these slope landscapes. The total N inventories showed similar spatial patterns to the inventories of 137Cs and SOC, and significant correlations were also found between the total N and 137Cs inventories in the SL, TL and GL. Therefore, 137Cs can successfully be used for tracing soil, SOC and total N dynamics within slope landscapes in the southeastern Tibetan Plateau.